Pemberian Fisioterapi Dada dan Suction terhadap Perubahan Kadar Saturasi Oksigen pada Pasien Gagal Nafas - S Sukhifah; N Sukesi; R Winarti; Wahyuningsih Wahyuningsih; C Hadi; W Heru (PPNI UNIMMAN, 2024)
Background: Respiratory failure is a condition in which the respiratory system fails to perform the function of gas exchange, namely the entry of oxygen and the exit of carbon dioxide. Patients with respiratory failure are usually put on a ventilator. Patients who are put on a ventilator will experience a buildup of secretions, to overcome this, chest physiotherapy and suction will be performed. Chest physiotherapy is a procedure performed on patients who experience secretion retention and oxygenation disorders who require assistance to thin or remove secretions. While suction is the act of inserting a suction catheter tube through the mouth or nose or endotracheal tube (ETT) which aims to reduce sputum retention, free the airway and prevent lung infections. The purpose of this community service is to teach and understand changes in oxygen saturation levels in patients with respiratory failure in the ICU room of the Dr. Ario Wirawan Salatiga Lung Hospital after chest physiotherapy and suction interventions. The methods used are training, lectures and direct demonstrations. The number of patients in this community service is 4 patients. The results of this community service are the effect of increasing oxygen saturation after chest physiotherapy and suction. That is, before chest physiotherapy, the average oxygen saturation level was 93%, after chest physiotherapy for 3 days it became 97%. While before suction, the average saturation level was 95%, after suction for 3 days the 4th saturation became 100%. The conclusion is that there is an increase in oxygen saturation levels after chest physiotherapy and suction in patients with respiratory failure in the ICU Room of the Dr. Ario Wirawan Salatiga Lung Hospital.